Peran Representasi Wanita dalam Dewan terhadap Keputusan Leverage pada Industri Maskulin di Indonesia - Caitlyn Naomi Chandra; Luky Patricia Widianingsih; Cliff Kohardinata Kohardinata (Politeknik Ganesha Medan, 2026)
The development of corporate governance has increased attention toward gender diversity within corporate boards, particularly in masculine industries traditionally dominated by men. This study examines the effect of Women on board of directors and commissioners on leverage policy in Indonesian masculine industry companies during the 2023-2024 period. The population comprised 87 mineral and non-mineral energy sector companies listed on TradingView. After applying purposive sampling criteria, 161 firm-year observations were obtained from 87 companies over a two-year period, following the exclusion of 13 observations due to outlier problem. Secondary data were obtained from companies’ annual reports and a quantitative approach was employed using multiple linear regression analysis. ang was proxied by Debt to Equity Ratio (DER), while Return on Assets (ROA) and firm size were included as control variables. Result shows that female representation on the board of commissioners has a significant negative effect on DER with a significance level of 4.6%, indicating that female commissioners tend to encourage more prudent financing policies and lower debt utilization. In contrast, female representation on the board of directors does not significantly affect DER. In addition, ROA negatively influences DER, while firm size demonstrates a positive relationship with DER. These results suggest that the supervisory role of female commissioners contributes more effectively to conservative leverage decisions than the managerial role of female directors, thereby highlighting the importance of women commissioners in strengthening leverage policies within masculine industries in Indonesia.